2018
DOI: 10.3949/ccjm.85a.17034
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine: An old drug with new relevance

Abstract: Hydroxychloroquine is an immunomodulatory drug that has been used for 60 years to treat malaria and autoimmune diseases such as systemic lupus erythematosus and inflammatory arthritis, and potential new uses and benefits continue to emerge. Toxicity concerns have been addressed with updated prescribing recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 49 publications
1
101
0
5
Order By: Relevance
“…After quinacrine was introduced as an antimalarial agent in World War II, it has associated with yellowish discoloration of the skin and other side effects. As a result of quinacrine-associated adverse effects, other antimalarial agents including chloroquine and hydroxychloroquine (HCQ) were derived with extensive chemical modification [9]. HCQ is an older drug and still used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…After quinacrine was introduced as an antimalarial agent in World War II, it has associated with yellowish discoloration of the skin and other side effects. As a result of quinacrine-associated adverse effects, other antimalarial agents including chloroquine and hydroxychloroquine (HCQ) were derived with extensive chemical modification [9]. HCQ is an older drug and still used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine (HCQ) is an antimalarial drug which is also used to treat rheumatic diseases such as rheumatoid arthritis and systemic lupus erythematosus (SLE). It is derived from chloroquine and has been in use for over 60 years [42]. Its definite mechanism of action has yet to be elucidated but it appears to work through different pathways, inducing anti-inflammatory, anti-oxidant and anti-thrombotic effects [21].…”
Section: Administration Of Hydroxychloroquine In Pregnancymentioning
confidence: 99%
“…Hydroxychloroquine is an aminoquinoline-like chloroquine (Furst, 1996). It is a drug commonly prescribed for the treatment of uncomplicated malaria, rheumatoid arthritis, chronic discoid lupus erythematosus, and systemic lupus erythematosus (Shippey et al, 2018). Chloroquine and hydroxychloroquine are being investigated for the treatment of SARS-CoV-2 (Devaux et al, 2020), and they have been reported to have direct antiviral effects, such as inhibition of flaviviruses, retroviruses (like HIV), and many coronaviruses.…”
Section: Discussionmentioning
confidence: 99%